Identification of future environmental challenges in Pakistan by 2025 through environment foresight - Waris Ali Gabol; Aleem Ahmed (African Journal of Environmental Economics and Management, 2019)
Technology foresight is defined as “the process involved in systematically attempting to look into the longer term future of science, technology, the economy and society with the aim of identifying the areas of strategic research and the emerging generic technologies likely to yield the greatest economic and social benefits.” Technology foresight on environment sector was carried out under the supervision of Pakistan Technology Board on the theme “Environment 2025: Our future, our choices”. Social, technological, environmental, economical, political and values (STEEPV) is an internationally recognized tool for brainstorming used in conducting technology foresight worldwide and was used by environment panel for collection of issues and drivers, opinions, policies and projects for future of environment in Pakistan. More than 20 experts participated in the expert panel brainstorming workshops. A diverse panel was formed with representation from R and D organizations, Ministry of Environment, researchers and professors in universities, NGO and private sector organizations. A consensus was achieved by the panel on top four most important issues in environment sector which include; (a) water (b) loss of biodiversity, (c) solid waste and (d) energy. Furthermore, the causes, remedies, policy recommendations and project proposals were identified for each of the four issues.